LC3A positive "stone like structures" are differentially associated with survival outcomes and CD68 macrophage infiltration in patients with lung adenocarcinoma and squamous cell carcinoma. (June 2021) - Gachechiladze, M.; Uberall, I.; Skanderova, D.; Matchavariani, J.; Ibrahim, M.; Shani, I.; Smickova, P.; Kolek, V.; Cierna, L.; Klein, J.; Stahel, R.; Joerger, M.; et al.
Highlights: LC3A positive Stone Like Structures (SLSs), are significantly associated with poor overall and disease free survival in patients with lung adenocarcinoma (LADC). In contrast, LC3A positive SLSs are associated with better overall and disease free survival in lung squamous cell carcinoma (LSCC). Analysis of LC3A mRNA expression from KMplotter, is consistent with our survival analysis. LC3A SLSs are positively associated with CD68 macrophage count in LADC, whereas SLS are negatively associated with CD68 macrophage count in LSCC. Abstract: Aims: The aim of the study was to analyse the prognostic and predictive value of LC3A positive' 'Stone Like Structures'' (SLSs) in a large cohort of patients with non-small cell lung carcinoma (NSCLC) and to check its relationship with tumor infiltrating lymphocytes (TILs) and PD-L1 expression. Methods: Tissue microarrays from 1015 patients diagnosed at the Institute of Pathology and Molecular Pathology, University Hospital Zurich, Switzerland, were stained for LC3A, PD-L1, CD3 and CD68 using automated tissue stainer Ventana Benchmark Ultra (Roche). TILs were assessed in matched haematoxylin and eosin stained slides. Results: LC3A positive SLSs, were significantly associated with worse overall (OS) and disease-free survival (DFS) outcomes in patients with lung adenocarcinoma (LADC) (HR = 2.4, 95 %CI(.994–1.008, p = 0.029) and HR = 3.9, 95 %CI (1.002–1.014), p = 0.002 respectively), whilst it was associated with better OS and DFS in patients with lung squamous cell carcinoma (LUSC), with marginal significance (HR = .99, 95 %CI(.975–1.011), p = 0.042 and HR = .99, 95 %CI (.975–1.008), p = 0.026). Multivariate analysis showed that LC3A SLSs are independent poor prognostic factor only in patients with LADC. In addition, LC3A SLSs, were negatively associated with CD68 count in LADC, whilst there was a positive correlation in LSCC. Conclusions: LC3A SLSs are differentially associated with the survival outcomes and CD68 count in LADC and LSCC. Further studies are justified for the understanding the underlying biological mechanisms of this phenomenon.